Duruoz Hand Index: Is it valid and reliable in children with unilateral cerebral palsy? - ŞANAL TOPRAK, CANAN; DURUÖZ, MEHMET TUNCAY; KARADAĞ SAYGI, NAİME EVRİM (TAYLOR & FRANCIS INC, 2019)
Purpose: To investigate the validity and reliability of the Duruoz Hand Index (DHI) in patients with unilateral cerebral palsy (CP). Methods: Assessments of patients (n = 23) were performed using the Modified Ashworth Scale (MAS), the Manual Ability Classification System (MACS), the grip and pinch strength tests, and DHI. Following the data collection, retest of DHI was administered telephonically within a 2-week period. Results: Test-retest reliability and internal consistency of DHI were found to be excellent with a Cronbach's alpha value of 0.93 and an intraclass correlation coefficient value of 0.94. The correlation between the DHI and MACS was detected significantly high (r = 0.840, p = < 0.010). The DHI also correlated with grip and pinch strength in the affected side (r = -0.459, p = r = -0.509, p = < 0.050). Conclusions: DHI is a valid and reliable questionnaire for patients with unilateral CP.
Keywords: Assessment of hand function; Duruoz Hand Index; reliability; unilateral cerebral palsy; validity; CLASSIFICATION-SYSTEM MACS; UPPER EXTREMITY; RELIABILITY; VERSION; SCALE